The Legal Status of the Sanitary Hygiene Feasibility Certificate as a Consumer Protection Instrument in Cloud Kitchen Operations - Sabrina, Amanda Feby; Surahmad (Journal of Law, Politic and Humanities, 2025)
This research examines the legal status of the Sanitation Hygiene Eligibility Certificate as an instrument of consumer protection in the operation of Cloud Kitchen businesses in Indonesia. The background of this study arises from the increasing trend of online food consumption that is not yet fully supported by adequate guarantees of hygiene and food safety. The purpose of this research is to analyze the dual function of the Sanitation Hygiene Eligibility Certificate as an administrative licensing requirement and as a preventive legal instrument that ensures consumers’ rights to safe and proper food. The research method used is normative juridical with a statutory approach, focusing on the analysis of laws, government regulations, and ministerial decrees related to food safety and consumer protection. The findings indicate that the absence of a Sanitation Hygiene Eligibility Certificate or the negligence of business actors in maintaining hygiene standards may result in civil liability based on unlawful acts under Article 1365 of the Indonesian Civil Code. The conclusion emphasizes the necessity of strengthening regulations and integrating digital licensing systems to ensure that the Sanitation Hygiene Eligibility Certificate functions effectively as a legal instrument for consumer protection in the digital economy era.